Holographic Duality and the Physics of Consciousness - Awret, Uziel (Frontiers in Systems Neuroscience, 2022)
This paper introduces a novel dual-aspect theory of consciousness that is based on the principle of holographic-duality in modern physics and explores the prospects of making philosophically significant empirical discoveries about the physical correlates of consciousness. The theory is motivated by an approach that identifies certain anti-physicalist problem intuitions associated with representational content and attempts to provide these with a consciousness-independent explanation, while suspending questions about the hard problem of consciousness and the more problematic ‘phenomenal character’. Providing such topic neutral explanations is ‘hard’ enough in the sense that solving it would make a philosophical difference and yet ‘easy’ enough to be approached scientifically. I will argue that abstract algorithms are not enough to solve this problem and that a more radical ‘computation’ that is inspired by physics and that can only be realized in ‘strange metals’ is needed. While speculative, this approach has the potential to both establish necessary connections between conscious mental states and the physical substrate ‘generating’ them and explain why this representational content is ‘nowhere to be found’. I will end with a reconsideration of the conceivability of zombies.